Correlation of Anxiety Disorder and Quality of Life in Systemic Lupus Erythematosus Patients - Kemala Emrizal; Laniyati Hamijoyo; Lynna Lidyana (Indonesian Journal of Rheumatology, 2019)
Background: Systemic Lupus Erythematosus (SLE), an autoimmune disease, can cause damage and impairment in the nervous system. Patients who had any manifestation of neurology can be classified as patients with Neuropsychiatric Systemic Lupus Erythematosus (NPSLE). One of the most frequent NPSLE manifestation is anxiety disorder. The presence of anxiety disorder is believed to be correlated with their ability to carry out daily activities. This study aims to see the correlation between anxiety disorder and quality of life (QOL) in patients with SLE. Method: an analitic cross-sectional study was done. The data were collected by distributing validated questionnaires to patients diagnosed with SLE in the outpatient clinic of dr. Hasan Sadikin General Hospital. Quality of life and anxiety disorder was measured using Short From-36 (SF-36) and Zung Self-Rating Anxiety Scale (Zung-SAS), respectively. Normality test was done before correlating the variables using Pearson method. Result: Forty-six SLE patients fitted with the inclusion criteria were participated in the study. The assessment using Zung-SAS showed that 9 (19.56%) correspondents had mild–moderate anxiety, and 1 (2.17%) had severe anxiety. The analysis of SF-36 showed the means of Physical Component Summary (PCS) and Mental Component Summary (MCS) which were 45.18 ± 8.23 and 47.11± 9.78, in order. The correlation test of Zung-SAS with PCS and MCS showed the result of r= -0.651 (p < 0,01) and -0.654 (p < 0,01), respectively. Conclusion: There is a significant negative correlation between anxiety disorder and QOL in patients with SLE. The result of this study showed that the high degree of ones anxiety was in a parallel line with their low level of QOL, so it is important to do an early detection and prevention of anxiety disorder in SLE patients. Keywords: Anxiety disorder, quality of life, Systemic Lupus Erythematosus, Zung Self Rating Anxiety Scale.